THE ROLE OF TRAINING IN IMPROVING THE ENTREPRENEURSHIP COMPETENCY OF SUSTAINABLE REHABILITATION PARTICIPANTS BNN WEST JAVA - Yelli Eka Sumadhinata; Nabilah Ramadhan; Yana Hendayana; Wien Dyahrini; Sri Wiludjeng; Suskim Riantani (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Darma Agung (LPPM_UDA), 2023)
Currently, the government is actively promoting empowerment programs for new entrepreneurs to boost the country's economy. However, for fellow participants in ongoing rehabilitation for clients assisted by BNN West Java Province, entrepreneurship activities can be a way to start a new life so that they can re- mingle and be well received by the community. This study aims to determine the effect of entrepreneurship training in improving entrepreneurial competence in sustainable rehabilitation participants for clients assisted by BNN West Java Province. The results of research using SPSS software show that entrepreneurship training has a significant effect on increasing entrepreneurial competence with an effect of 65.9%. The results of this study are expected to provide motivation for the government, the private sector, and other organizations to be able to organize entrepreneurship training with better quality so that this training can help fellow participants in sustainable rehabilitation in preparing themselves to become part of the community again through entrepreneurial activities.